Removal of large fibrotic bladder blood clots using prostatic tissue morcellator under real-time ultrasound guidance - Wu, Ronghua; Shang, Yonggang; Liu, Xing; Chen, Wei; Yi, Shanhong (Frontiers in Surgery, 2022)
Objective Large fibrotic bladder blood clots are difficult to treat via conventional methods. Hence, we investigated the safety and reliability of real-time ultrasound guidance combined with prostate tissue morcellator in the removal of large fibrotic bladder blood clots in this study. Methods We chose 9 patients with large fibrotic bladder blood clots who were treated in our department from January 2019 to December 2020. Under the condition that conventional methods were ineffective in removing the bladder blood clot, real-time ultrasound guidance combined with a prostatic tissue morcellator was used to remove the large fibrotic bladder blood clot through the steps of positioning, breaking, adjusting repositioning and recrushing. After removal, the bipolar electrocautery was replaced to stop bleeding of the bladder mucosa. Results All patients successfully underwent the operation. After the blood clot was removed, the bladder mucosa was examined. There was no damage to the bladder mucosa or muscle layer. The urine was clear at the end of the procedure with slow irrigation, and no bleeding was found again. Conclusion Real-time ultrasound guidance combined with a prostate tissue morcellator was a safe, effective and quick method for the removal of large fibrotic bladder blood clots.